Integrating STEAM4Innovator Learning, Gamification, and Design Thinking to Enhance Students’ Innovative Skills - Prayoonphokkharat, Poom (SEAQIS Journal of Science Education, 2025)
This study aimed to develop an integrated learning approach that combines STEAM4Innovator, gamification, and design thinking to enhance students' innovative skills. The approach was created through a four-step process, including empathising and defining insights with learners, ideating and generating WOW! ideas, prototyping and developing a business model, and testing and producing the final solution. The approach was implemented with 109 Year 12 students, and the results indicated substantial improvements in their academic performance (78.47% improvement), innovative skills (62.09% improvement), and satisfaction with the learning process (86.97 out of 100), thereby highlighting the effectiveness and appeal of proposed approach. In addition, the success of approach is attributed to its capacity to foster learning and innovation skills, namely inspiration, imagination, creativity, integration, and hands-on implementation. This study demonstrates the effectiveness of integrating STEAM4Innovator, gamification, and design thinking in enhancing learning outcomes and encouraging the development of innovative skills.